REAL COMMUNICATION : HOW TO BE YOU AND LEAD TRUE - Dolan, Gabrielle, author (Milton, Qld. : John Wiley & Sons Australia, 2019)
A rapidly evolving workplace and disruptive technologies have created a growing demand for transparency and authenticity in communication from business leaders. Yet many decision-makers find themselves far behind the curve when it comes to understanding and meeting the evolving expectations of employees and customers. Real Communication: How to Be You and Lead True reveals how to guide and communicate in a way that is authentic and will help business leaders truly connect and engage with their teams, customers, and coworkers.